[entre]margens poéticas e pedagógicas (Revista Apotheke, 2022)
This paper presents the (in)tense relations between the poetic and the pedagogical, which were experienced during the process of a teaching undergraduate course, and also aims at contributing to the production of a difference of meaning in the teacher training. In the form of an essay, it proposes the intertwining with philosophy and literature, and resulted from meetings held during the curricular structured teacher training, when students were challenged to think a poetic work inspired in pedagogical projects and in reports about educational works which are required for the professional performance in schools. In order to cause a difference in the ways of living life and teaching, these propositions, shaped as artistic publications, were meant to act as devices to make holes in the standard teaching representation, which is usually built in the training process.
Keywords: Pedagogical; Poetic; Teacher training; Difference